The Long and Winding Road: Archiving and Re-Using Qualitative Data from 12 Research Projects Spanning 16 Years. (June 2021) - Dodds, Catherine; Keogh, Peter; Bourne, Adam; McDaid, Lisa; Squire, Corinne; Weatherburn, Peter; Young, Ingrid
We describe a pilot project designed to assess the feasibility of re-use across 12 diverse qualitative datasets related to Human Immunodeficiency Virus (HIV) in the UK, from research projects undertaken between 1997 and 2013 – an approach which is chronically underused. First, we consider the sweeping biomedical changes and imperatives relating to HIV in this time frame, offering a rationale for data re-use at this point in the epidemic. We then reflexively situate the processes and procedures we devised for this study with reference to relevant methodological literature. Hammersley's and Leonelli's contributions have been particularly instructive through this process, and following their lead, we conclude with further considerations for those undertaking qualitative data re-use, reflecting on the extent to which qualitative data re-use as a practice requires attention to both the given and the constructed aspects of data when assembled as evidence.